1998
DOI: 10.1021/bi972861z
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the B-Myb DNA-Binding Domain:  A Possible Role for Conformational Instability of the Protein in DNA Binding and Control of Gene Expression,

Abstract: Double- and triple-resonance heteronuclear NMR spectroscopy have been used to determine the high-resolution solution structure of the minimal B-Myb DNA-binding domain (B-MybR2R3) and to characterize the specific complex formed with a synthetic DNA fragment corresponding to the Myb target site on the Myb-regulated gene tom-1. B-MybR2R3 is shown to consist of two independent protein domains (R2 and R3) joined by a short linker, which have strikingly different tertiary structures despite significant sequence simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…At the end of the procedure (cycle 7) unique assignments were obtained for 94.3% (1498/ 1589) of the NOE peaks picked in the 15 N/ 1 H NOESY-HSQC spectrum and 96.3% (4030/4184) of those identified in the 13 C/ 1 H HMQC-NOESY spectrum. This level of success compares very favorably with our experience of manual iterative assignment of NOE peaks in protein spectra (42,43,47), and the automatic approach took only a few days as compared with several months for manual assignment. The uniquely assigned NOE peaks produced 2845 non-redundant 1 H to 1 H upper distance limits, which were used as the principle constraints in the final rounds of structural calculations.…”
Section: Resultssupporting
confidence: 64%
“…At the end of the procedure (cycle 7) unique assignments were obtained for 94.3% (1498/ 1589) of the NOE peaks picked in the 15 N/ 1 H NOESY-HSQC spectrum and 96.3% (4030/4184) of those identified in the 13 C/ 1 H HMQC-NOESY spectrum. This level of success compares very favorably with our experience of manual iterative assignment of NOE peaks in protein spectra (42,43,47), and the automatic approach took only a few days as compared with several months for manual assignment. The uniquely assigned NOE peaks produced 2845 non-redundant 1 H to 1 H upper distance limits, which were used as the principle constraints in the final rounds of structural calculations.…”
Section: Resultssupporting
confidence: 64%
“…This property has been reported for a number of protein and nucleic acid binding sites on proteins (31,32) and may be an important factor controlling the specificity of the binding interaction. It has been shown by Kay and co-workers (33,34) that the flexible region of the peptide binding site in the phospholipase C-␥1 SH2 domain has a much wider ligand binding specificity than the more rigid phosphotyrosine binding site.…”
Section: Backbone Mobility Of the Binding Site For N-mmp-3-thementioning
confidence: 68%
“…1C 32 -Asn 33 in the AB ␤-hairpin were also marginally above the threshold (mean plus 1 standard deviation) considered to be significant (Fig. 1C).…”
Section: Resultsmentioning
confidence: 84%
“…Interestingly, in vitro translated full-length B-Myb did not bind to Myb binding site in the SV40 promoter, but the C-terminal truncation mutants of BMyb or B-Myb DNA binding domain fused to c-Myb were able to bind the same sequences suggesting that C-terminus of B-Myb exerts additional limitation to DNA binding . Third, the NMR structure for the DNA binding domain of B-Myb revealed that despite extensive sequence similarity in the R2 and R3 regions, the C-terminal region of BMyb R2 shows a poorly de®ned structure, re¯ecting the existence of multiple conformations in slow to intermediate exchange (McIntosh et al, 1998). This contrasts with the tertiary structure reported for c-Myb R2R3, in which both R2 and R3 have the same folding and the C-terminal region of R2 forms a stable, wellde®ned helix (Ogata et al, 1994).…”
Section: Sequence Recognition By Myb Dna Binding Motifmentioning
confidence: 99%